2016
DOI: 10.3389/fpsyg.2016.01476
|View full text |Cite
|
Sign up to set email alerts
|

Lay Evaluation of Financial Experts: The Action Advice Effect and Confirmation Bias

Abstract: The goal of this experimental project was to investigate lay peoples’ perceptions of epistemic authority (EA) in the field of finance. EA is defined as the extent to which a source of information is treated as evidence for judgments independently of its objective expertise and based on subjective beliefs. Previous research suggested that EA evaluations are biased and that lay people tend to ascribe higher EA to experts who advise action (in the case of medical experts) or confirm clients’ expectations (in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…recommended maintaining the status quo) or gave no recommendation at all (Barnoy, Levy, & Bar‐Tal, ; Barnoy, Ofra, & Bar‐Tal, ; Bar‐Tal, Stasiuk, & Maksymiuk, ; Stasiuk, Bar‐Tal, & Maksymiuk, ). Similar results were reported by Zaleskiewicz, Gasiorowska, Stasiuk, Maksymiuk, and Bar‐Tal (), who studied how consumers perceive the EA of financial advisors and showed that individuals attributed greater authority to those consultants who advised action in the context of considering whether to take out a mortgage. However, the latter authors also preliminarily documented that assigning greater authority to experts recommending action might result from consumers' desire to reach congruence between their own opinions and expert recommendations.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…recommended maintaining the status quo) or gave no recommendation at all (Barnoy, Levy, & Bar‐Tal, ; Barnoy, Ofra, & Bar‐Tal, ; Bar‐Tal, Stasiuk, & Maksymiuk, ; Stasiuk, Bar‐Tal, & Maksymiuk, ). Similar results were reported by Zaleskiewicz, Gasiorowska, Stasiuk, Maksymiuk, and Bar‐Tal (), who studied how consumers perceive the EA of financial advisors and showed that individuals attributed greater authority to those consultants who advised action in the context of considering whether to take out a mortgage. However, the latter authors also preliminarily documented that assigning greater authority to experts recommending action might result from consumers' desire to reach congruence between their own opinions and expert recommendations.…”
Section: Introductionsupporting
confidence: 84%
“…In the first step, the minimal sample size for Experiment 1 and for the two other experiments was calculated. Zaleskiewicz et al (), who previously investigated determinants of EA evaluation in finance, reported a medium sized (partial η 2 = .116, p < .001) interaction effect of participants' opinions and experts' recommendations on the evaluation of financial experts' EA. Therefore, in order to determine the sample size in the present project, we conducted a priori power analyses using G*Power (Faul, Erdfelder, Lang, & Buchner, ).…”
Section: Methodsmentioning
confidence: 98%
“…Consistent with Messick's (2009) statement that "making personnel decisions on the basis of race, gender, ethnicity, or other 'irrelevant' factors is unethical" (p. 73, emphasis added), the existing literature largely examines gender and ethical issues in the performance evaluations context, including evaluating leadership (Hoyt et al, 2009;Koenig et al, 2011), assignment of audit client portfolio (Hardies et al, 2020), as well as evaluating sell-side equity analysts for promotion (Bloomfield et al, 2020) and compensation (Lin & Neely, 2017) among others (see meta-analysis by Koch et al, 2015). Our study extends prior gender and ethics literature beyond the evaluation setting to a judge-advisor setting (Yaniv, 2004;Zaleskiewicz et al, 2016;Baeckstrom et al, 2018; for a review of the judge-advisor paradigm, see Guntzviller et al, 2020), where individual investors rely on and process the advice provided by an expert (i.e., an equity analyst) to make investment decisions.…”
Section: Ingroup Favoritism In the Judge-advisor Contextmentioning
confidence: 74%
“…Our recent research (Zaleskiewicz & Gasiorowska, 2018; Zaleskiewicz, Gasiorowska, Stasiuk, Maksymiuk, & Bar-Tal, 2016) has shown that decision-makers, when evaluating the financial expertise of prospective advisors, are vulnerable to preferring advice that is consistent, as opposed to inconsistent, with their own beliefs. In brief, we investigated how financial recommendations concerning individual investing on the stock market were perceived depending on whether they were, or were not, consistent with laypeople’s own opinions of this financial activity (Zaleskiewicz & Gasiorowska, 2018).…”
Section: Confirmation Effect In Evaluating Financial Experts’ Authoritymentioning
confidence: 99%
“…In our prior research exploring the role of the confirmation effect in evaluating financial experts’ authority (Zaleskiewicz & Gasiorowska, 2018; Zaleskiewicz et al, 2016), we suggested that people are motivated to ascribe greater authority to those experts whose advice confirms their own opinions for three different reasons. First, devaluing the competence of those experts whose recommendations are inconsistent with one’s own beliefs might be an effective strategy to defend self-esteem.…”
Section: Psychological Mechanisms Behind Confirmation Effect In Evalu...mentioning
confidence: 99%